2013
DOI: 10.1089/cap.2011.0136
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Neutropenia in Clozapine-Treated Children and Adolescents with Childhood-Onset Schizophrenia

Abstract: Our study shows that the rates of neutropenia in clozapine-treated children and adolescents are considerably higher than in the adult population. Younger age, African American ethnicity, and male gender were significant risk factors. These are also risk factors for benign neutropenia in healthy children and adolescents. Despite these high rates of neutropenia, all but one of the patients with neutropenia during hospitalization were successfully discharged on clozapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
(43 reference statements)
0
13
0
1
Order By: Relevance
“…Therefore, p53 expression after melphalan exposure is a potential biomarker corresponding to clinical response to melphalan, which is in agreement with our modeling results. Furthermore, previous articles reported gender and ethnicity as risk factors for neutropenia after other chemotherapies. Our model also indicates that gender and race could explain portions of IIV for SLOPE and MTT, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, p53 expression after melphalan exposure is a potential biomarker corresponding to clinical response to melphalan, which is in agreement with our modeling results. Furthermore, previous articles reported gender and ethnicity as risk factors for neutropenia after other chemotherapies. Our model also indicates that gender and race could explain portions of IIV for SLOPE and MTT, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hematologic abnormalities induced by antipsychotics may be life-threatening in some patients. Several studies revealed the association between clozapine and leukopenia in children, and clozapine is generally recommended for drug-resistant cases 26 - 28 . In addition, Etain et al reported that leukopenia was induced by risperidone 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Among a sample of 87 children and adolescents being treated with Clozapine, approximately half of them displayed mild to moderate neutropenia, which is much higher than the risk of neutropenia among adults. There appears to be certain risk factors that can increase the likelihood of developing this complication, including younger age, being male and being an African-American (Maher et al, 2013 ). There continues to be disagreement around the efficacy of typical versus atypical antipsychotic medication in the treatment of schizophrenia.…”
Section: Treatmentmentioning
confidence: 99%